2017
DOI: 10.1155/2017/6512620
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Delivery of miR-146a Mimics Delayed Seizure Onset in the Lithium-Pilocarpine Mouse Model

Abstract: Unveiling the key mechanism of temporal lobe epilepsy (TLE) for the development of novel treatments is of increasing interest, and anti-inflammatory miR-146a is now considered a promising molecular target for TLE. In the current study, a C57BL/6 TLE mouse model was established using the lithium-pilocarpine protocol. The seizure degree was evaluated according to the Racine scale, and level 5 was considered the threshold for generalized convulsions. Animals were sacrificed to analyze the hippocampus at three tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 43 publications
0
39
0
Order By: Relevance
“…miR-146a is 100% conserved between humans and mice; it is expressed broadly in the brain during embryonic development and restricted to neurons at postnatal stages. Importantly, modulating the expression of this particular miRNA was shown to reduce the latency, the duration as well as the intensity of the induced epilepsy in rodent models of telencephalon epilepsy [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…miR-146a is 100% conserved between humans and mice; it is expressed broadly in the brain during embryonic development and restricted to neurons at postnatal stages. Importantly, modulating the expression of this particular miRNA was shown to reduce the latency, the duration as well as the intensity of the induced epilepsy in rodent models of telencephalon epilepsy [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…treating patients with pre-existing, refractory epilepsy) 17 , we found eight up- and one down-regulated miRNAs common to all three models (Figure 3B,C). This included miR-132-3p and miR-146a-5p, for which there is already significant functional data linking them to epilepsy 2528 , and six miRNAs (miR-10a-5p, miR-21a-3p, miR-27a-3p, miR-142a-5p, miR-212-3p and miR-431-5p) for which there is limited or no functional in vivo data linking to epilepsy (Figure 3C).…”
Section: Resultsmentioning
confidence: 99%
“…Lack of complement inhibition can lead to a state of chronic inflammation, not uncommonly found in brains from patients with refractory epilepsy (Vezzani and Viviani, 2015). Future work is needed to reconcile the proseizure functions of miR-146a reported by He et al, with the anti-seizure and -epilepsy functions observed in two other studies (Iori et al, 2017b;Tao et al, 2017).…”
Section: Mir-146amentioning
confidence: 93%
“…Two recent studies showed a seizure‐suppressing effect of miR‐146a supplementation. Intranasal administration of a miR‐146a mimic delayed seizure onset in a lithium‐pilocarpine rat model of TLE (Tao et al, ), and intracerebroventricular injection of a miR‐146a mimic before or after kainic acid‐mediated induction of status epilepticus delayed seizure onset and reduced seizure frequency in mice (Iori et al, ). Iori et al demonstrated that modulation of miR‐146a through intracerebroventricular injection of a mimic 24 hrs and 72 hrs before induction of kainic acid‐induced status epilepticus in mice decreased the time spent in seizure in addition to reducing the overall number of seizures.…”
Section: Candidate Micrornas With Therapeutic Potential In Epilepsy Amentioning
confidence: 99%
See 1 more Smart Citation